Desigualdade numa escola em mudança : trajetórias e embates na escolarização pública de jovens pobres - Ferreira, Mônica Dias Peregrino (2008)
This thesis proposes to unmask the relationship between the scholar institution and poor youngsters that begin to inhabit the school due the démarche of its expansion. The question put is: how do we universalize the public school system in a country that has systematically refused the complete integration of the major proportion of the poor population? The research occurred in a public school faced as a particular case of what is possible (Bourdieu) brought into analysis three decades of the students trajectories and performed a deep journey through different styles of scholar processes. Through this axles it became possible to understand, at the same time, old and new inequalities that mark the recent history of Brazilian urban schools. Selection, segregation, belonging and regulation are categories that support the development of this analysis, that turns the scholar institution into a sigh seeing from which it is possible to capture some elements that compose the social dynamics.